Building Information Model–based finite element analysis of high-rise building community subjected to extreme earthquakes. Issue 4 (March 2019) - Ren, Xiaodan; Fan, Weida; Li, Jie; Chen, Jun
Starting from the Building Information Model, a pre-processing procedure is proposed in this work to develop the refined finite element model of buildings and building community. The structural members which are represented by three-dimensional solid entities in Building Information Model are converted to lines and planes according to their geometric characteristics. To meet the requirements of finite element analysis of building structures, the lines are discretized by the beam elements and the surfaces are discretized by the shell elements. The damage plasticity model is implemented to simulate the damage and failure of concrete, and the classic plasticity model is chosen for steel. The simulations of high-rise building and building community are performed with the help of large computing server. The damage patterns of different building structures are obtained and discussed. This study lays a solid foundation for the further fusion between Building Information Model and finite element analysis.